Pendidikan Demokrasi dalam Kurikulum Bermuatan Ideologi pada Institusi Pendidikan Islam - Umar Samsudin (Eduprof : Islamic Education Journal, 2020)
Education as a major factor in the development of people's culture is often used by various thoughts and ideologies to spread their understanding and thinking patterns. It is not strange if a thought dominates a certain educational institution or system. Among the ideas that influence and even determine the goals and learning methods of an educational system are ideology and religion. The relationship between education and ideology is rooted in the history of education. The domination of an ideology is not only obtained through revolution or violence carried out by state institutions, but also through other institutions, such as religious institutions, education, mass media and the family. And it becomes clear that the nature of education is very dependent on the perspective of the ideology it adopts. Abstrak Pendidikan sebagai faktor utama perkembangan budaya masyarakat, seringkali dimanfaatkan oleh berbagai pemikiran dan ideologi untuk menyebarkan pemahaman dan pola pikirnya. Sudah tidak asing lagi jika suatu pemikiran mendominasi lembaga atau sistem pendidikan tertentu. Di antara pemikiran-pemikiran yang banyak memberikan pengaruh dan bahkan menentukan tujuan dan metode pembelajaran suatu sistem pendidikan adalah ideologi dan agama. Hubungan antara pendidikan dan ideologi sudah mengakar dalam perjalanan sejarah dunia pendidikan. Dominasi suatu ideologi tidak hanya didapatkan melalui revolusi atau kekerasan yang dilakukan oleh institusi-institusi negara, tetapi juga dapat melalui institusi-institusi lain, seperti institusi agama, pendidikan, media massa dan keluarga. Dan menjadi jelaslah bahwa hakikat pendidikan sangat tergantung dari kacamata ideologi yang dianutnya.